Antidepressant-like effects of menhaden fish oil in postpartum-induced model of depression in rats - Arbabi, Leila (2014)
Postpartum depression (PPD) is a psychiatric disorder that defined as a subtype of major depressive disorder (MDD) which may result from reproductive hormone fluctuations subsequent to childbirth. Approximately 10-15% of women experience postpartum depression (PPD) after baby delivery. It is hypothesized that the depression symptoms may be attenuated with omega-3 fatty acids. In order to examine this hypothesis, ovariectomized female rats underwent hormone-simulated pregnancy (HSP) regimen and received progesterone and estradiol benzoate or vehicle for 23 days, mimicking the actual rat’s pregnancy. Forced feeding of menhaden fish oil (rich in omega-3) with three doses of 1, 3 and 9 g/kg/d, fluoxetine (an antidepressant drug) 15mg/kg/d and distilled water 2ml/d per rat started in six experimental groups on postpartum day 1 and continued for 15 consecutive days. On postpartum day 2, 8 and 15 all groups were tested in the forced swimming test (FST) and open field test (OFT). The seventh experimental group (normal control), which had not experienced neither ovariectomy nor injection, received only distilled water 2ml/d through oral gavage for 15 consecutive days and underwent the same behavioral tests as well. Animals were sacrificed by decapitation on postpartum day 15 following exposure to behavioral tests and blood and brain samples were collected. Plasma samples were utilized to assay levels of corticosterone and pro-inflammatory cytokines using ELISA and Procarta immunossay technique respectively. The corticosterone levels of hippocampus were measured by ELISA as well. Significant differences between groups were evaluated using one-way analysis of variance (ANOVA), followed by the post hoc Tukey’s multiple comparison test when appropriate P<0.05 was considered significant. The results showed that following 15 consecutive days’ treatment with three different doses of menhaden fish oil, the immobility time of animals seen in FST was reduced compared to negative control group. The effect was found to be dose dependent where menhaden fish oil 3g and 9g/kg/d have shown significant reduction in immobility time. Furthermore, menhaden fish oil did not change locomotor activity; therefore, the decrease of immobility time observed in FST following menhaden fish oil supplementation is due to its ability to attenuate depression. The results of biochemical analysis showed that the plasma levels of corticosterone, interleukin 1-β and interferon-γ were decreased significantly following menhaden fish oil treatment at doses of 3 and 9 g/kg/d. In addition, supplementation with 9 g/kg menhaden fish oil significantly decreased the plasma levels of tumor necrosis factor-α and hippocampal levels of corticosterone. However, menhaden fish oil at 1 g/kg produced a slight reduction (p>0.05) in immobility time in FST and in the levels of corticosterone and pro-inflammatory cytokines. Taken together, these results suggest that menhaden fish oil, rich in omega-3, exerts beneficial effect on postpartum depression and decreases the biomarkers related to depression.